2021
DOI: 10.3390/agronomy12010013
|View full text |Cite
|
Sign up to set email alerts
|

Compost Based on Pulp and Paper Mill Sludge, Fruit-Vegetable Waste, Mushroom Spent Substrate and Rye Straw Improves Yield and Nutritional Value of Tomato

Abstract: Plant biomass in the form of waste materials and by-products from various industries can be a valuable material for the production of composts and growing media for urban gardening. In this study, pulp and paper mill sludge, fruit-vegetable waste, mushroom spent substrate and rye straw were used to produce compost that was further used as a medium component in container cultivation of tomato. The plants were grown in containers with a capacity of 3 dm3 filled with three types of compost-based growing media sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Huang et al 2019 [33] showed that tomato plants grown in BC-compost mixtures produced a larger amount of fresh and dry fruit biomass; the authors attributed the result to the synergistic effect of the two materials, whereby compost increased nutrients availability while biochar provided a high nutrient-retention capacity. Similarly, Zawadzi ńska et al [43] attributed the higher fresh tomato weights of compost growing media to the greater availability and uptake of nutrients. Although the influence of biochar on growing substrate properties and plant growth has been widely studied [17,19,49], little is known about the effects on horticultural fruit production.…”
Section: Fruit Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…Huang et al 2019 [33] showed that tomato plants grown in BC-compost mixtures produced a larger amount of fresh and dry fruit biomass; the authors attributed the result to the synergistic effect of the two materials, whereby compost increased nutrients availability while biochar provided a high nutrient-retention capacity. Similarly, Zawadzi ńska et al [43] attributed the higher fresh tomato weights of compost growing media to the greater availability and uptake of nutrients. Although the influence of biochar on growing substrate properties and plant growth has been widely studied [17,19,49], little is known about the effects on horticultural fruit production.…”
Section: Fruit Productionmentioning
confidence: 98%
“…Lazcano et al [36] also observed the highest increase in root volume with compost dilution ranging between 10% and 20% in compartmentalized grown tomato plants. A compost addition of up to 30% in growing media has been reported to improve total pore space and organic matter content, promoting root development [43]. Moreover, compost nutrients and phytohormones induce root tip proliferation, improving root volume [31].…”
Section: Plant Developmentmentioning
confidence: 99%
“…Secondary clumping occurred in the peat and the proportion of fractions > 3 mm was the highest (37.0%). In the study by Zawadzinska et al 63 , the share of fractions below 1 mm ranged from 20% in compost to 29–42% in substrates with compost mixtures. A larger share of finer fractions favourably affects the increase in water capacity of the substrate 64 .…”
Section: Discussionmentioning
confidence: 92%
“…A horticultural substrate consisting of a peat mixture with the addition of wood fibre compost provided a high yield of fruit of comparable or higher nutritional value than in peat substrates 63 . According to the authors, the higher nutrient content and their availability to the tomato plants and the larger pore space had a beneficial effect on the yield of this species and the quality of its fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation